Estimating Core Inflation - The Role of Oil Price Shocks and Imported Inflation - Hilde Christiane Bjørnland (Statistics Norway, Research Department, 1997)
This paper calculates core inflation, by imposing long run restrictions on a structural vector autoregression (VAR) model containing the growth rate of output, inflation and oil prices. Core inflation is identified as that component in inflation that has no long run effect on output. No restrictions are placed on the response of output and inflation to the oil price shocks. The analysis is applied to Norway and the United Kingdom, both oil producing OECD countries. A model that distinguishes between domestic and imported inflation, is also specified for Norway. In both countries, core inflation is a prime mover of CPI (RPI) inflation. However, CPI (RPI) inflation overvalues or undervalues core inflation in many periods, of which oil price shocks are important sources behind this deviation for prolonged periods
Keywords: C32; E31; E61; 330; Core inflation; inflation target; long-run neutrality; oil price shocks; imported inflation; structural VAR.